Multiple Role of Bhimal in the farming systems of Garhwal hills - Kashyap, Poonam; Gangwar, B.; Prusty, A. K.; Singh, M. P.; Singh, V. K.; Chaudhary, V. P. (Indian Farming, 2017)
The economy of the hills is mainly dependent on agroforestry system for meeting their requirement of food, fuel, medicinal plants, and nontimber products and fodder for livestock rearing. An indigenous agro-forestry system not only supports the livelihood through production of food, fodder and firewood but also mitigates the adverse impact of climate change through carbon sequestration. The system of growing trees in combination with agriculture needs to be maintained, especially in the hills. This will not only help in maintaining the land stability but also in protection from soil erosion for sustained development in the region.